PENERAPAN TEKNIK PEMBELAJARAN RODA KEBERUNTUNGAN TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI IPS SMAN 16 PADANG TAHUN PELAJARAN 2013/2014 - Afrianti, Gezi; Longgom. Nst, Minora; Mardiyah, Ainil (Pendidikan Matematika, 2014)
ABSTRACTÂ This research is motivated by the students understanding of mathematical concept are still low and studentsâ not interest in learning mathematical. This research was aimed to determine whether studentsâ understanding of mathematical concept by implementing the wheel of fortune learning technique better than the studentsâ understanding of mathematical concept than the implementing of conventional learning in class XI IPS SMAN 16 Padang school year 2013/2014. This was an experimentasl research and applied random research toward the subject. Based on the perceived data analysis, the class sample has normally distributed and homogeneus. Hypothesis test result obstained P-value = 0,009 was smaller than Â then reject , so the research hypothesis was accepted.Â  It can be concluded that the studentâs understanding of mathematical concept by implementing the wheel of fortune learning technique better than the studentsâ understanding of mathematical concept than the implementing of conventional learning in class XI IPS SMAN 16 Padang school year 2013/2014.Â